Impact of GP gatekeeping on quality of care, and health outcomes, use, and expenditure: a systematic review - Sripa, Poompong (Br J Gen Pract, 2019)
BACKGROUND: GPs often act as gatekeepers, authorising patients’ access to specialty care. Gatekeeping is frequently perceived as lowering health service use and health expenditure. However, there is little evidence suggesting that gatekeeping is more beneficial than direct access in terms of patient- and health-related outcomes. AIM: To establish the impact of GP gatekeeping on quality of care, health use and expenditure, and health outcomes and patient satisfaction. DESIGN AND SETTING: A systematic review. METHOD: The databases MEDLINE, PreMEDLINE, Embase, and the Cochrane Library were searched for relevant articles using a search strategy. Two authors independently screened search results and assessed the quality of studies. RESULTS: Electronic searches identified 4899 studies (after removing duplicates), of which 25 met the inclusion criteria. Gatekeeping was associated with better quality of care and appropriate referral for further hospital visits and investigation. However, one study reported unfavourable outcomes for patients with cancer under gatekeeping, and some concerns were raised about the accuracy of diagnoses made by gatekeepers. Gatekeeping resulted in fewer hospitalisations and use of specialist care, but inevitably was associated with more primary care visits. Patients were less satisfied with gatekeeping than direct-access systems. CONCLUSION: Gatekeeping was associated with lower healthcare use and expenditure, and better quality of care, but with lower patient satisfaction. Survival rate of patients with cancer in gatekeeping schemes was significantly lower than those in direct access, although primary care gatekeeping was not otherwise associated with delayed patient referral. The long-term outcomes of gatekeeping arrangements should be carefully studied before devising new gatekeeping policies.